Improvement for performance radio frequency in wireless communication based on impulse signal - Jafaar Fahad A. Rida (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This research presents the improved performance of mobile wireless communication channel is based on non-line of sight because the mobile propagation channel is very hard to work with direct path between the transmitter and mobile receiver because of city-based area has objects such as rise building, trees, surround structures, and other objects. The mobile wireless spread radio channels have radio propagation mechanisms as a reflection, diffraction, and scattering effect on radio signal as lessening, and distortion or spread time. The most important thing to make real is that the wireless channel is a multipath radio channel. Multipath copies of the same signal with distinct amplitudes, stages and delay times for all multipaths between the transmitter and the receiver. The multipath fading is defined by its impulse response, which includes the facts about the relative time of the recipient's arrival of various indices of multipath additives. The impulse response expresses great characteristics in the time domain such the large bandwidth frequencies and the amplitude output only the value impulse response δ(t) equal to one when the value of time t=0, otherwise,  the value impulse response δ(t) equal to zero in all values of the time. Over a time period reaction, the cellular radio channel could be designed as a linear filter with various impulses.